Organizational Actorhood and the Management of Paradox: A Visual Analysis. Issue 5 (June 2018) - Halgin, Daniel S.; Glynn, Mary Ann; Rockwell, Dean
We extend the theorization of organizations as social actors to illuminate how external attributions of actorhood are made by the business media and how these attributions are associated with heightened environmental paradoxes confronting organizations. We analyze the visual depictions of organizations on 530 covers of an influential periodical, BusinessWeek (BW) magazine, over a 30-year period, 1978–2007. We present evidence that the visual depiction of organizational actorhood increased over time and that this depiction occurred more frequently in periods characterized by heightened paradoxical tensions in the business environment. Moreover, we find that in these periods, there is a complementarity between the visual and verbal modes: verbal text highlights the oppositional nature of paradox while the visual image offers interpretations for the management of these tensions. Our work contributes to understanding how the visual construction of organizations by external audiences can position the organization's standing as an actor, as well as the organization's capabilities for action under conditions of environmental challenge.